Building knowledge systems in agriculture: Five key areas for mobilising the potential of extension and advisory services: Position paper: June 2012 - Global Forum for Rural Advisory Services (International Food Policy Research Institute, 2012)
There is renewed attention on the importance of advisory services and extension in rural development processes. This paper, based on the publication ‘Mobilizing the potential of rural and agricultural extension', focuses on five opportunities to mobilise the potential of extension and advisory services. The five areas are: (1) focusing on best-fit approaches; (2) embracing pluralism; (3) using participatory approaches; (4) developing capacity; and (5) ensuring long-term institutional support.